Super Encryption with Hill Cipher and Myszkowski Transposition for Android Multimedia Files Security - Aldi Febriayanto; Eko Hari Rachmawanto (Politeknik Negeri Batam, 2026)
This research aims to design, implement, and evaluate an Android-based data security application called Secure Vault using a super encryption method that combines Hill Cipher (substitution) and Myszkowski Transposition (transposition). The background of this research is motivated by the increasing number of cyberattacks on Android devices, particularly those targeting multimedia data. The method used is Research and Development with the Waterfall model. A total of 300 synthetic multimedia files (images, videos, documents, texts) were encrypted and decrypted using three methods: Hill Cipher alone, Myszkowski Transposition alone, and super encryption. Testing included computational time, Shannon entropy values, black box testing (15 scenarios), User Acceptance Test (UAT) with 30 respondents, and statistical analysis (ANOVA, Pearson correlation, paired t-test). The results showed that super encryption produced an average encryption time of 7.56 seconds and the highest entropy increase (0.92 bits/byte, approaching 92.8% of the maximum 8 bits/byte). The encryption/decryption success rate for valid files reached 100%, with a black box pass rate of 90.3%. The UAT obtained an average score of 3.90/5 (Good category). The Pearson correlation between file size and encryption time was very strong (r = 0.939, p < 0.001). The conclusion of this research is that super encryption effectively enhances multimedia data security on Android with high entropy and perfect functional success, although there is a trade-off in processing time that remains acceptable. The Secure Vault application is feasible for protecting personal data.